Pharmacokinetics and safety of the two oral cefaclor formulations in healthy chinese subjects in the fasting and postprandial states - Qu, Xinyao; Deng, Qiaohuan; Li, Ying; Li, Peng; Liu, Guangwen; Wang, Yanli; Liu, Zhengzhi; Yu, Shuang; Cheng, Yang; Zhou, Yannan; Chen, Jiahui; Ren, Qing; et al. (Frontiers in Pharmacology, 2022)
Abstract We conducted a phase I bioequivalence trial in healthy Chinese subjects in the fasting and postprandial states. The goal of this trial was to compare the pharmacokinetics and safety of the test preparation Cefaclor granule (Disha Pharmaceutical Group Co., Ltd.) and the reference preparation Cefaclor suspension (Ceclor®, Eli Lilly and Company). In this trial, 24 subjects were selected in the fasting and postprandial states, respectively. Enrolled subjects randomly accepted a single dose of 0.125 g Cefaclor granule or Cefaclor suspension. The washout period was set as 2 days. Blood samples were collected within 8 h after administration in the fasting state and within 10 h after administration in the postprandial state. Plasma concentrations were determined by Liquid chromatography-tandem mass spectrometry (LC-MS/MS). Pharmacokinetic parameters (AUC, Cmax) were used to evaluate bioequivalence of the two drugs. In the fasting trial, the geometric mean ratios (90% confidence intervals CIs) for Cmax, AUC0-t, and AUC0-∞ were 93.01% (85.96%-100.63%), 97.92% (96.49%-99.38%) and 97.95% (96.52%-99.41%), respectively. The GMR (90% CIs) for Cmax, AUC0-t, and AUC0-∞ in postprandial state were 89.27% (81.97%-97.22%), 97.31% (95.98%-98.65%) and 97.31% (95.93%-98.71%), respectively. The 90% CIs of AUC and Cmax in the fasting and postprandial states were within the 80-125% bioequivalence range. Therefore, Cefaclor granule and Cefaclor suspension were bioequivalent and displayed similar safety profiles. Furthermore, food intake affected the pharmacokinetic parameters of both drugs.